Penerapan Cost Volume Profit Sebagai Dasar Perencanaan Laba pada Usaha Kedai Panji & Swimming Pool - Luh Intan Putri Pratiwi; Ni Made Wulan Sari Sanjaya (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This research using Cost Volume Profit (CVP) analysis was conducted with the aim of finding out the basic steps in profit planning at Kedai Panji & Swimming Pool. The main problems faced by the business are the absence of a structured profit planning system and fluctuating visitor numbers. This research method uses quantitative descriptive through data collected in the form of interviews, documentation, and analysis of financial statements for the year 2024. The results show that the contribution margin ratio is 59.25%, the break even point is Rp244,895,110, and the margin of safety is 17.93%. The degree of operating leverage is recorded at 560%, indicating that small changes in sales have a significant impact on profit. The 2025 profit target of Rp40,000,000 can be achieved with a sales target of Rp312,603,983. By applying Cost Volume Profit (CVP) analysis, Kedai Panji & Swimming Pool can plan profits more systematically, improve cost management efficiency, and optimize sales strategies to achieve sustainable business growth.